Trout residues silage in the feeding of fattening sheep - Parisuaña Callata, Juan (2018)
The effect of the level of inclusion of trout residues silage (ERT) on lamb ration on daily feed intake (CMD), daily gain (GMD), feed efficiency (ICA) and the taste of lamb meat was evaluated. Thirty lambs were distributed in three treatments (0, 4 and 8% ERT) considering 5 replicates per treatment. At the end of the experiment (84 days) the lambs were slaughtered, and a taste panel evaluation was performed. The results showed that the highest level of ERT in the ration reduced CMD (2.08, 2.01 vs. 1.65 kg/day for 0, 4 and 8% for ERT, respectively, p<0.001) and GMD (0.25, 0.28 vs 0.23 kg/day, p<0.03), while the ICA improved (8.49 vs. 7.28, 7.07 kg:kg, p<0.001). In addition, the inclusion of ERT in the ration did not affect the taste of lamb meat. It is concluded that the ERT in the fattening rations of sheep improves the productive yield without affecting the taste of the meat.